EFFORT FOR EMPOWERMENT OF RESILIENT EDUCATION IN THE MIDDLE OF THE COVID 19 PANDEMIC AND LIMITATIONS OF FACILITIES IN STATE ELEMENTARY SCHOOL 3 CIJEMIT - Rachma Sri Utami (Widyagogik, 2021)
Education is an important aspect for everyone. However, not a few people can experience an education that is fulfilled by the adequacy of good facilities to support the acquisition of knowledge in school. This condition, of course, gave birth to various obstacles which are the shared responsibility of every element in the field of education, especially the Government in responding to the continuity of the teaching and learning process in schools optimally. In this case, the Government needs to empower the education aspect, especially in frontier, remote and underdeveloped schools. No wonder the education gap in the area is still the center of attention today, due to the lack of balance in the provision of educational service facilities. In this regard, this community service activity focuses on seeking various learning methods at elementary schools that have low accreditation and are located in frontier, remote and disadvantaged areas. One of them is at State Elementary School 3 Cijemit, Ciniru District, Kuningan Regency to provide learning innovation services for students. The school has limited facilities to support learning. Aspects that are focused on are: (1) innovation in teaching and learning activities, (2) technology adaptation, (3) school administration, (4) providing library facilities, and (5) implementation of work programs. The method used refers to the MBKM program. In its implementation, these five aspects can provide synergy to support the provision of optimal educational services.